PTH-098 Connecting liver and gut in psc: ccl25 expression is upregulated in colitis, correlates with inflammatory activity and facilitates effector ccr9+ lymphocyte recruitment. (22nd June 2015) - Trivedi, PJ; Bruns, T; Ward, ST; Mai, M; Schmidt, C; Hirschfield, G; Weston, C; Adams, D
Abstract : Introduction: Recruitment of mucosal T-cells to the liver in response to aberrantly expressed homing signals drives hepatobiliary inflammation in primary sclerosing cholangitis (PSC). This is exemplified by the 'gut-homing' chemokine CCL25, which recruits intestinal CCR9 + effector cells to the PSC liver. However, previous studies report CCL25 expression as being confined to the small bowel whereas PSC is typically associated with colonic inflammation. Our aim was to determine whether CCL25 and CCR9 are expressed in the inflamed human colon in patients with colitis. Method: Mucosal biopsies were obtained during surveillance colonoscopy (n = 40) and colonic tissue from patients undergoing surgical resection for colitis (n = 6), or non-colitis-associated cancer (n = 5). CCL25 mRNA was evaluated by qRT-PCR (relative to GUSb) and protein expression confirmed using western blotting and tissue-ELISA. Lymphocyte CCR9 expression was quantified by flow cytometry, and the ability of sorted a4b7 + CCR9 + and a4b7 + CCR9 - T-cells to transmigrate across hepatic sinusoidal endothelium (HSEC) investigated in flow-based adhesion assays. Results: CCL25 mRNA and protein were absent from normal colon but present in colitis. CCL25 mRNA expression correlated with endoscopic Mayo score (p = 0.001) and tissue levels of TNFa (Spearman's rho 0.811; p < 0.0001) as indices of inflammatory activity (Figure 1) . In colitis, >90% of CD3 + CD4 + and >15% of CD8 + T-cells expressed CCR9 (6% and 2% in normal colon; p = 0.01 and 0.03) and were predominantly CD127 + effector lymphocytes. a4b7 + CCR9 + T-cells showed enhanced adhesion and transendothelial migration across HSEC compared with a4b7 + CCR9 - T-cells (p < 0.05). Conclusion: CCL25 is expressed in the inflamed human colon, correlates with inflammatory activity and is associated with high frequencies of CCR9 + tissue-infiltrating lymphocytes. These findings lend further support to the mucosal lymphocyte homing hypothesis of PSC and show how it can be applied to patients with colitis. Disclosure of interest: None Declared.